Correction: The absolute configurations of hyperilongenols A–C: rare 12, 13-seco-spirocyclic polycyclic polyprenylated acylphloroglucinols with enolizable β, β′-tricarbonyl systems from Hypericum longistylum Oliv. Issue 10 (30th April 2019) - Zhang, Na; Shi, Zhengyi; Guo, Yi; Xie, Shuangshuang; Qiao, Yuben; Li, Xiao-Nian; Xue, Yongbo; Luo, Zengwei; Zhu, Hucheng; Chen, Chunmei; Hu, Linzhen; Zhang, Yonghui
Abstract : Correction for 'The absolute configurations of hyperilongenols A–C: rare 12, 13- seco -spirocyclic polycyclic polyprenylated acylphloroglucinols with enolizable β, β′-tricarbonyl systems from Hypericum longistylum Oliv.' by Na Zhang, et al., Org. Chem. Front., 2019, DOI: 10.1039/c9qo00245f.